Construction and optimization of a smart classroom system for emotional computing - HUANG Lijuan; CHENG Zhengyi; YANG Ziyan (物联网学报)
In the context of the deep integration of new generation information technology and smart education, the research and application of smart classroom systems have received widespread attention. However, the current application of smart classroom systems is still in its early stages, lacking real-time feedback and real-time positive intervention functions for students. To solve this problem, a smart classroom system based on emotional learning was built, and edge computing was introduced to improve the real-time and intelligent level of the classroom, so as to achieve real-time feedback of students' emotional state during learning. Secondly, to improve the performance of the smart classroom system, convex optimization theory was utilized to optimize the allocation of system resources. Finally, through verification, the multiple resources joint optimization method of the smart classroom system can effectively reduce the maximum delay of device data collection and processing, greatly improve the real-time performance of emotional computing in the smart classroom system, and avoid blindly pursuing the minimum average delay, effectively avoiding the situation where a single user experienced poorly due to poor real-time performance. Overall, the system and algorithm achievements have reference and significance for the construction of future smart classrooms.